The Incense Port of Moscha (Khor Rori) in Dhofar - Pirenne, Jacqueline (The Journal of Oman Studies, 1975)
The site of Khor Rori was excavated by an expedition from the American Foundation for the Study of Man in three seasons: April 1952-Fcbruary 1953, February 1958 and January 1962. Two inscriptions from the site have been published: one a dedication to the god Sin on a bronze plaque, and the other an inscription of quite late date in three fragments.